Solubility and Dissolution Rate Enhancement of Ketoprofen by Nanoparticles - Fatimah Mohammed Hussein Wais (Institute of Medico-legal Publications Pvt Ltd, 2020)
Reduction in particles size cause increase in effected surface area of drug particle. So as dissolutionoccurred at the surface of solute, rapid increase in dissolution rate due to large surface area. Ketoprofenbelong to class II according Biopharmaceutics Classification System in which has low solubility and highpermeability.the aim of study was to enhance solubility as well as dissolution rate of Ketoprofen whenpreparation of Ketoprofen nanoparticles by solvent evaporation method. Different formula of Ketoprofennanoparticles were prepared using different type of polymers (pvpk15,HPMCK15, MCA4C,and CMC 30) .All of the prepared Ketoprofen nanoparticles formulas showed a particle size result within nano-range withentrapment efficiency ranged from (85.7% to 98.3 %). The average particle size of Ketoprofen nanoparticleswas observed from (55 nm to 995 nm). The selected formula was investigation for DSC, PXRD, FTIR,SEM, entrapment efficiency and invitro drug release. The invitro dissolution study showed a significant(p<0.01) enhancement in dissolution rate of nanoparticles formula as compared to pure Ketoprofen (drug alone) and physical mixture(drug and stabilizer), at 10 min. 75.7% of drug release from nanoparticles, whileonly 15.2%, 22.7% for pure ketoprofen and PM(drug: stabilizer), respectively.